INDICATING THE FINEST TREATMENT FOR CHRONIC FISSURE IN ANO - Sudesh, *Gupta; Bala, Madhu; Bhawana, Gupta; Manpreet, Singh (International Journal of Ayurveda and Pharma Research, 2017)
An anal fissure is a common, mostly benign, condition that can be acute or chronic. The diagnosis is usually made on history and physical examination, but further investigations are sometimes necessary. Primary fissures are usually benign and located in the posterior or anterior position. Secondary fissures are lateral or multiple and often indicate a more serious underlying pathology. Anal fissure is largely associated with high anal sphincter pressures and most treatment options are based on reducing anal pressures. Conservative management, using increased fiber and warm baths, results in healing of approximately half of all anal fissures. New therapies include perineal support devices, Gonyautoxin injection, fissurectomy, fissurotomy, sphincterolysis, and flap procedures. Further research is required comparing these new therapies with existing established therapies. New therapies are not suitable as first line treatments, though they can be considered if conventional treatment fails. In fissures if conservative care fails, various pharmacologic and surgical options offer satisfactory cure rates. Lateral internal sphincterotomy remains the gold standard for definitive management of anal fissure. This review outlines the key points in the presentation, pathophysiology, and management of anal fissure.